Prospective evaluation of complications associated with transesophageal echocardiography in dogs with congenital heart disease. (8th January 2022) - Stoner, Caitlin H.; Saunders, Ashley B.; Heseltine, Johanna C.; Cook, Audrey K.; Lidbury, Jonathan A.
Abstract: Background: Transesophageal echocardiography (TEE) is useful in the assessment and procedural monitoring of congenital heart disease (CHD) with a relatively low complication rate in humans. Objectives: To evaluate the safety of TEE and report complications in dogs. Animals: Forty client‐owned dogs with CHD. Methods: Prospective observational study including gastroesophagoscopy before and after TEE imaging. TEE was planned with a GE 6VT‐D adult probe in dogs weighing ≥4 kg and a GE 10T‐D microprobe alternating with an intracardiac echocardiography probe placed in the esophagus in dogs <4 kg. Difficulties with probe placement, probe interference and TEE probe imaging times were recorded. Dogs were monitored in the recovery period after TEE using an established nausea scoring system. Results: New gastroesophageal abnormalities were identified after TEE in 4 dogs including 4 areas of mucosal damage involving <25% of the lower esophageal sphincter (n = 4) and 1 lesion at the heart base (n = 1) and were not attributed to longer imaging times or a specific probe. Lesions identified before TEE in 4 dogs remained unchanged after TEE. The 6VT‐D probe could not be placed in 1 dog with enlarged tonsils, and it obstructed fluoroscopic views in 3 dogs. The probes did not compress any structures in dogs in which fluoroscopy was performed (n = 20). Four dogs had evidence to suggest nausea after the procedure. Conclusions and Clinical Importance: While major complications remain possible, complications in this study were mild and few in number. Dog size and probe characteristics are factors to consider when performing TEE.